Breaking Out of Open-Plan: Extending Social Interference Theory Through an Evaluation of Contemporary Offices. Issue 9 (November 2020) - Davis, M. C.; Leach, D. J.; Clegg, C. W.
Offices are evolving rapidly to facilitate organizational cost reductions and to better support contemporary working practices. We investigate relationships between the design of contemporary offices (physical proximity and breakout areas) and autonomy in predicting individual outcomes (ease of communication, job satisfaction, and well-being). We extend Social Interference Theory to include features of contemporary office design and explicitly explore the moderating role of autonomy. Working in differing office configurations of a global engineering company, 406 employees provided data. Access to breakout areas was strongly related to ease of communication, higher job satisfaction, and well-being. In the absence of breakout areas, employees with higher autonomy were able to better manage the challenges arising from contemporary offices. Practical implications include incorporating breakout areas to enhance employee experience within open-plan offices, using job design to optimize employee experience in open-plan offices, and manager and employee involvement in office design.